Study on organic goat production as a tool for sustainability of nomadic pastoralism in north-western Himalayan region, India - THAKUR, ANKAJ; SHARMA, ANURAG; SHARMA, MANOJ; KUMAR, ATUL; PRASAD, C K; SHARMA, AKSHAY; VANITA, BRIJ (The Indian Journal of Animal Sciences, 2024)
Migratory Gaddi sheep and goat constitutes approximately 70% of the total population of small ruminants in Himachal Pradesh, which is in north-western Himalayan region of India. The present investigation was carried out on 32 Gaddi migratory flocks consisting of around 5000 animals (sheep and goat) through structured pre-validated questionnaire to find out scope of nomadic pastoralism for organic goat production. Through cross-sectional surveys, it was found that 100% of breeds reared by the nomads are indigenous in origin, which is well adapted for grazing and browsing in different hilly terrains and topographies. Tethering was not at all practiced among the nomadic flocks of goats. The flocks were herd in corrals during night to prevent predatory loss. The main source of nutrition for goats was rangeland, natural pastures and common property resources. The nomadic goat production system does not substantially compromise the welfare of the animals. Natural suckling and freedom of social behaviour in nomadic flocks are the ethological advantages same as that are required for standards of organic production. Natural breeding is commonly practiced in this nomadic goat production system whereas artificial insemination, embryo transfer and estrus synchronization is unpopular. Ethno-veterinary practices of Gaddi farmers give them an edge over other countries in organic goat production; it can be effective substitute for allopathic medicines but needs to be validated on efficacy and dosage. Exploring and supporting nomadic pastoralism for organic production will help in improving its traceability, meeting consumer satisfaction and sustaining the dwindling nomadic pastoralism.